ANALISIS PENGARUH KEPUASAN MAHASISWA TERHADAP PROSES PEMBELAJARAN SECARA E-LEARNING - Haryadi Sarjono (Business Management Journal, 2017)
One of the strategies in improving satifaction of clients is getting direct input from customers (which in this case, students of Management Departement, UBM) through questionnaires on the process of studying by e-learning. The type of this research is descriptive research which makes use of a descriptive survey. The results of this research show that the majority of customers are not satified on some aspects of studying by e-learning. The biggest gap there is in indicator 7, namely the lecturers are lazy in using e-learning for the teaching-learning process. By using Cartesius diagram, it is found that the indicators in quadrant A are 6,7 and 11, for quadrant B: 1, 4, 5, 9, 10 and 12, while for quadrant C: 2, 3, and 8. There is no indicators in quadrant D. Keywords : Customer Satifaction, Cartesius Diagram, Teaching Process, E-learning.